2014
DOI: 10.3892/ijo.2014.2727
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitor induces autophagy and apoptosis in osteosarcoma cells

Abstract: Heat shock protein 90 (Hsp90) is constitutively expressed at 2-10-fold higher levels in tumor cells compared to normal cells, suggesting that it may be critically important for tumor cell growth and survival. These features make Hsp90 a potential target for anticancer drug development. Inhibition of Hsp90 activity not only results in rapid degradation of Hsp90 client proteins but also induces apoptosis of various tumor cells. Hsp90 also plays an important role in autophagy. An Hsp90 inhibitor induces autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 31 publications
6
65
0
Order By: Relevance
“…These include genes involved in the insulin signaling pathway [23], proteins associated with cell proliferation [24], and estrogen and progesterone receptor subtypes [25]. In the present study, five proteins (lamin A, vimentin, tubulin-β chain, ANXA6, and SERPINC1) were reported previously, [22] and thirteen proteins were identified for the first time being differentially expressed in PCOS as compared to the normal ovaries.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These include genes involved in the insulin signaling pathway [23], proteins associated with cell proliferation [24], and estrogen and progesterone receptor subtypes [25]. In the present study, five proteins (lamin A, vimentin, tubulin-β chain, ANXA6, and SERPINC1) were reported previously, [22] and thirteen proteins were identified for the first time being differentially expressed in PCOS as compared to the normal ovaries.…”
Section: Discussionsupporting
confidence: 63%
“…HSP90B1 is demonstrated to be involved in the growth of cancerous cells, and HSP90B1 inhibitors can reverse cancer cell growth and increase survival [2429]. HSP90B1 is an important chaperone protein that interacts with multiple intracellular receptors and transcription factors, has a role in stabilization of client proteins from protease degradation, such as AKT, I ĸB-α, glucocorticoid, and progesterone receptors [24, 25, 30], and responsible for client protein stability and maturation after activation [31]. However, the underlying molecular mechanisms of HSP90B1 on ovarian cell function remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a protective role when cells encounter environmental stresses, such as starvation or pathogen infection [34, 35]. This type of autophagy benefits cell survival, but excessive autophagy can result in autophagic cell death [36].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the combination of GA and the autophagy inhibitor 3-MA could significantly enhance GA-induced apoptosis and suppress autophagy [50]. Undoubtedly, these also demonstrate that Hsp90 can regulate autophagy.…”
Section: Hsp90 Inhibition For Cancer Therapymentioning
confidence: 57%
“…Recently, it has been reported that GA induces autophagy by inhibiting the Akt/mTOR signaling pathway and induces a caspase-dependent apoptosis in osteosarcoma cells [50]. As expected, the combination of GA and the autophagy inhibitor 3-MA could significantly enhance GA-induced apoptosis and suppress autophagy [50].…”
Section: Hsp90 Inhibition For Cancer Therapymentioning
confidence: 90%